A statistical approach to determining energetic outer radiation belt electron precipitation fluxes. Issue 5 (21st May 2014) - Simon Wedlund, Mea; Clilverd, Mark A.; Rodger, Craig J.; Cresswell‐Moorcock, Kathy; Cobbett, Neil; Breen, Paul; Danskin, Donald; Spanswick, Emma; Rodriguez, Juan V.
Abstract Subionospheric radio wave data from an Antarctic‐Arctic Radiation‐Belt (Dynamic) Deposition VLF Atmospheric Research Konsortia (AARDDVARK) receiver located in Churchill, Canada, is analyzed to determine the characteristics of electron precipitation into the atmosphere over the range 3 < L < 7. The study advances previous work by combining signals from two U.S. transmitters from 20 July to 20 August 2010, allowing error estimates of derived electron precipitation fluxes to be calculated, including the application of time‐varying electron energy spectral gradients. Electron precipitation observations from the NOAA POES satellites and a ground‐based riometer provide intercomparison and context for the AARDDVARK measurements. AARDDVARK radiowave propagation data showed responses suggesting energetic electron precipitation from the outer radiation belt starting 27 July 2010 and lasting 20 days. The uncertainty in >30 keV precipitation flux determined by the AARDDVARK technique was found to be ±10%. Peak >30 keV precipitation fluxes of AARDDVARK‐derived precipitation flux during the main and recovery phase of the largest geomagnetic storm, which started on 4 August 2010, were >105 el cm−2 s−1 sr−1. The largest fluxes observed by AARDDVARK occurred on the dayside and were delayed by several days from the start of the geomagnetic disturbance. During the main phase of the disturbances, nightside fluxes were dominant. Significant differences in flux estimates between POES, AARDDVARK, and the riometer were found after the main phase of the largest disturbance, with evidence provided to suggest that >700 keV electron precipitation was occurring. Currently the presence of such relativistic electron precipitation introduces some uncertainty in the analysis of AARDDVARK data, given the assumption of a power law electron precipitation spectrum.